Water Quality in Satui River and Histological Structure Study of Liver of Baung Fish (Mystus nemurus) - Triana, Dinda; Santoso, Heri Budi; Kadarsah, Anang (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Satui River is a river that has quite dense activity along the river flow, this is thought to result in a decrease in the quality of river waters. Fish is one of the organisms that can be used in tests to determine some chemical contamination in an aquatic environment. Baung fish are widely found in the waters of the Satui river and baung fish is thought to have properties that are sensitive to environmental changes. Histopathological testing in fish can provide a picture of tissue changes such as the kidneys and liver. Preparation of histological preparations using the paraffin method. Water quality analysis is compared with PP Water Quality Standard No. 22 of 2021 and analyzed using the Pollution Index method. Qualitative histopathological analysis is carried out by descriptive and quantitative analysis using scoring. The conclusion of this study is that the quality of the satui river is classified as lightly polluted with a value of P1 1.11 and P2 2.31. Histopathological damage to the liver of baung fish includes fat degeneration, congestion and necrosis.